Multifaceted roles of SARM1 in axon degeneration and signaling - Waller, Thomas J.; Collins, Catherine A. (Frontiers in Cellular Neuroscience, 2022)
Axons are considered to be particularly vulnerable components of the nervous system; impairments to a neuron’s axon leads to an effective silencing of a neuron’s ability to communicate with other cells. Nervous systems have therefore evolved plasticity mechanisms for adapting to axonal damage. These include acute mechanisms that promote the degeneration and clearance of damaged axons and, in some cases, the initiation of new axonal growth and synapse formation to rebuild lost connections. Here we review how these diverse processes are influenced by the therapeutically targetable enzyme SARM1. SARM1 catalyzes the breakdown of NAD+, which, when unmitigated, can lead to rundown of this essential metabolite and axonal degeneration. SARM1’s enzymatic activity also triggers the activation of downstream signaling pathways, which manifest numerous functions for SARM1 in development, innate immunity and responses to injury. Here we will consider the multiple intersections between SARM1 and the injury signaling pathways that coordinate cellular adaptations to nervous system damage.